Road Performance Comprehensive Evaluation of Polymer Modified Emulsified Asphalt Fiber Microsurfacing - Yifeng Xia; Jie Jia; Qian Chen (Advances in Materials Science and Engineering)
To further improve the road performance of microsurfacing, two kinds of polymer modified emulsified asphalt and three kinds of fibers were selected to prepare a variety of microsurfacing mixtures. The composition of the microsurfacing was optimized and verified. The effects of polymer modified emulsified asphalt and fiber types on the road performance of the microsurfacing were analyzed. Based on TOPSIS method of entropy weight, the road performance of the microsurfacing was comprehensively evaluated, and the microsurfacing with the best comprehensive road performance was optimized. The results show that the addition of waterborne polyurethane can further improve the water stability and low-temperature crack resistance of the waterborne epoxy resin modified emulsified asphalt fiber microsurfacing. Adding fiber can effectively improve the road performance of the microsurfacing. After adding polypropylene fiber, the bonding performance and water damage resistance of polymer modified emulsified asphalt microsurfacing were improved to the maximum. After adding basalt fiber, the deformation resistance, the 60°C dynamic stability, and the −10°C splitting strength of polymer modified emulsified asphalt microsurfacing reached the maximum. Among the three fibers, polypropylene fiber microsurfacing has the best comprehensive road performance, followed by basalt fiber microsurfacing.